Commonplace book 1919-1953 - Moore, G. E. (Thoemmes Press, 1993)
A collection of notebooks which express the views of the English philosopher George Edward Moore. They deal with such subjects as the paradoxes of the Epimenides family, conditional and disjunctive statements.